Strengthening Character Education Modules for Teachers to Improve the Work Character of Vocational High School Students - Meutia, Tiara Osa; Dwikurnaningsih, Yari; Satyawati, Sophia Tri (Universitas Pendidikan Ganesha, 2023)
One of the objectives of national education is to prepare character education activities in the form of forming character and character for the next generation of the nation. At the vocational high school level, it does not only focus on building good character but also the character needed in the world of work. This study aims to develop a work character-based Strengthening Character Education program module that can improve the work character of vocational high school students. The type of research conducted is research and development (Research and Development) using the integration of the ADDIE model with Borg and Gall. Data collection techniques used are documentation studies, questionnaires, and interviews. Analysis of research and development data results using mixed methods with a concurrent mixed methods. Qualitative data analysis used the Miles and Huberman model while quantitative data analysis used quantitative descriptive techniques with percentages and mean. This research resulted in a work character-based strengthening character education module in Vocational High Schools. Based on field trials, it shows that the strengthening character education module is based on work character, with the trial results having a score of 85% in the valid category and can be used without revision. It is hoped that SMK teachers can utilize the module in implementing strengthening character education so that they can improve the quality of graduates, especially work character.